Interaction of Additive Manufacturing and Forming - Merklein, Marion; Dubjella, Patrick; Schaub, Adam; Butzhammer, Lorenz; Schmidt, Michael (Proceedings of 6th International Conference on Additive Technologies, 2016)
Titanium alloys such as Ti-6Al-4V are utilized for a wide range of industrial approaches. This is primarily due to their positive material characteristics such as high biocompatibility, good corrosion resistance and outstanding specific strength. As a result of the hexagonal close packed (hcp) grain structure the achievable plastic deformation of these alloys at room temperature is limited. To overcome these limitations, forming at elevated temperatures is a promising process. A further promising manufacturing method for titanium is laser beam melting (LBM). LBM functions at melted material condition and thereby neglects most manufacturing challenges. It enables to produce individual parts by overcoming geometrical design restrictions compared to conventional manufacturing techniques. Within this work a process chain combining sheet metal forming and laser beam melting is presented and discussed. The main benefit of this combined process is a merge of the positive  characteristics of both manufacturing methods. In former researches deep drawing was used as forming process. Due to inducing a more complex stress level, which is more application oriented, bending will be investigated as a forming strategy for a combination with LBM. Therefore a tool was developed and manufactured. In this study the function of this tool will be described in detail and its qualification for bending flat sheets of Ti-6Al-4V as well as hybrid parts will be researched.
Keywords: Additive Manufacturing; Forming; Bending; Titanium alloys